The recreational activities of Philippine Science High School students as related to certain variables - Pasao, Myrna (Maria Myrna Adoracion Manzano) (s.n.], 1968)
The study analyzed some variables like creativity potential, nature of the entrance test scores, academic grades, and recreational interests of Philippine Science High School students and the relationships of these variables to each other in order to formulate a recreation program specifically for the Philippine Science High School. Defined in terms of specific recreational activities, sociability level of the activities, and the recommended sponsoring agency, the proposed program is an attempt to tap the scientific, social, and artistic creativity potentials of the students.